The Impacts of Relational Norms and Relationship Quality in to Franchisee's Loyalty - Ishak, Khairol Anuar (International Review of Management and Marketing, 2016)
The organizations have shifted from transactional to relational approach in maintaining their relationship in inter-organization partnerships and collaborations. The concept of relationship quality (RQ) evolved from relational marketing theory, and provided the impetus for a paradigm shift from transactional relationships to be more cooperative and service-centred relationships in business-to-business (B2B) processes. RQ has been considered as a key component in most relationship marketing such as buyer-seller, exporter-importer and franchisor-franchisee. This study examine empirically the relationship between RQ, relational mechanisms and loyalty in franchise system from a franchisee‘s perceptive in Malaysia. A total of 400 questionnaires were mailed by using random sample to a local-home grown franchisee. The results show that relational norms are positively influence the relationship quality of franchisor-franchisee relationship. In addition, relationship quality also found positively influenced franchisee loyalty to stay in franchise system. Keywords: Relationship quality, franchising, norms, communication and loyalty. JEL Classifications: D83, J53